Who’s Forest? Implications of Different Management Regimes for Sustainable Utilisation and Minimisation of Conflicts - Eastern and Central Africa Programme for Policy Analysis (ECAPAPA/ASARECA, 2005)
This Policy Brief presents some of the lessons learned from research work related to the search for appropriate mechanisms to manage forest resources, and conflicts arising from contested rights to forest resources in eastern and central Africa (ECA).